From vulnerability to resilience: Strengthening the mental health of Muslim migrant families in Auckland, New Zealand - Saputra, Wahyu Nanda Eka; Rohmadheny, Prima Suci; Santosa, Hardi (Universitas Muhammadiyah Magelang, 2025)
The high suicide rate in Auckland, New Zealand, poses a significant challenge for Muslim migrant families facing cultural pressures. This community Service program aims to strengthen their mental health through a structured series of workshops and psychoeducation sessions. The initial workshop focused on the basic understanding of mental health, risk factors for psychological disorders, and the familys role in resilience. Subsequent psychoeducation sessions presented practical strategies for stress management, emotion regulation, and coping mechanisms aligned with the cultural and religious values of the participants. Evaluation results demonstrated a significant increase in participants’ understanding of mental health and awareness of the risks of psychological disorders. Furthermore, participants showed improved ability to apply stress management strategies. This program contributes to enhancing the psychological well-being of Muslim migrant families while strengthening support systems within the community. The success of this activity is expected to serve as a foundation for broader and more sustainable similar interventions.